Nicanor Abelardo: Tagapagbunsod ng Modernismosa Klasikal na Musika sa Pilipinas - Santos, Ramon Pagayon (Musika Jornal; Vol 10 (2014), 2016)
Upon stepping on the soil of the United States of America, Nicanor Abelardo discovered a much larger realm of music creation, where he felt the freedom from the harmonic language which was being abandoned in Europe and the US in contemporary times. In the short time of his sojourn, he was able to master the techniques of modernism that was being practiced by Stravinsky, Bartok, Hindemith, and Schoenberg. As he was not interested in creating “isms”, he remained true to his own poetico-dramatic self and simply expanded the space by which he could communicate his inner soul with greater latitude and compass. This paper discusses four of his celebrated works, showing the different techniques, as well as his transcendence of stylistic distinctions towards the development of an individual and personal expression.